Analysis of Hospitality Management and Innovation as a Post Pandemic Recovery Effort in Bali - Milla Permata Sunny (Institute of Computer Science (IOCS), 2022)
The COVID-19 pandemic has hit the tourism sector and the hotel sector is no exception. This blow caused hotels in Bali to go out of business. Business managers in the hospitality sector must always adopt effective management strategies. Based on this review, this study aims to analyze the management and innovation of the hospitality sector as an effort to recover after the pandemic in Bali. This research is a descriptive qualitative research with data collection techniques through literature study with qualitative data analysis techniques. The results of this study conclude several management strategies and innovations carried out in the hospitality sector in Bali after the COVID-19 pandemic. This research is expected to be a recommendation material for hotel industry managers in developing a management model in the hospitality sector as an effort to recover after the pandemic.